1982
DOI: 10.1085/jgp.80.3.403
|View full text |Cite
|
Sign up to set email alerts
|

Monazomycin-induced single channels. I. Characterization of the elementary conductance events.

Abstract: Monazomycin (a positively charged, polyene-like antibiotic) induces voltage-dependent conductance changes in lipid bilayer membranes when added to one of the bathing solutions . These conductance changes have generally been attributed to the existence of channels spanning the membrane . In this article we characterize the behavior of the individual conductance events observed when adding small amounts of monazomycin to one side of a lipid bilayer . We find that there are several apparent channel types with one… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0

Year Published

1982
1982
2018
2018

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 17 publications
0
22
0
Order By: Relevance
“…Some have suggested that the helical dipole moment of the peptide chains lining the channel is a decisive determinant (23). It has also been argued that bound ions could supply the gating charge (24). Others have emphasized the potential role of charged groups on the side chains of the peptides (25).…”
Section: Discussionmentioning
confidence: 99%
“…Some have suggested that the helical dipole moment of the peptide chains lining the channel is a decisive determinant (23). It has also been argued that bound ions could supply the gating charge (24). Others have emphasized the potential role of charged groups on the side chains of the peptides (25).…”
Section: Discussionmentioning
confidence: 99%
“…The initial experiments (protocol I) were done using a low-pass integrator (Andersen and Muller, 1982) to obtain an analogue representation of the time-averaged single-channel current. The membrane potential was varied manually in 5-100-mV (usually 10-mV) steps, with 10-60-s sojourns at each level.…”
Section: Experimental Protocolsmentioning
confidence: 99%
“…An interesting alternative involves consideration of a second poorly understood property of the system, namely, the molecular basis for the voltagedependent shift in the probability of the two conducting states of the monazomycin channels (Andersen and Muller, 1982) . The most attractive interpretation of the shift is that it represents two different aggregation states of the channel such that an aggregate of lower molecularity becomes stabilized at high V.…”
Section: Voltage Dependence Of the Macroscopic Conductance Results Frommentioning
confidence: 99%
“…This is the second of two articles that describe the elementary events that underlie monazomycin-induced conductance (G) changes in planar lipid bilayers . In the preceding article (Andersen and Muller, 1982), we showed that the only characteristic of monazomycin channels that is not nearly invariant to changes in membrane potential (V) is the frequency of occurrence of the channels (f) . The purpose of this paper is to show that variations in channel frequency are indeed the basis for the voltage dependence of the monazomycin conductance .…”
Section: Introductionmentioning
confidence: 99%